Motives for choosing, switching and stopping daily or event‐driven pre‐exposure prophylaxis – a qualitative analysis. Issue 10 (14th October 2019) - Zimmermann, Hanne ML; Eekman, Sanne W; Achterbergh, Roel CA; Schim van der Loeff, Maarten F; Prins, Maria; de Vries, Henry JC; Hoornenborg, Elske; Davidovich, Udi; ,
Abstract: Introduction: In settings where both daily and event‐driven pre‐exposure prophylaxis (PrEP) are offered to men who have sex with men (MSM), a clear understanding of the motives to choose between the different dosing‐regimens can facilitate more effective PrEP implementation. We therefore studied the motives for choosing for, switching between, and stopping daily or event‐driven PrEP. Methods: We used data (August 2015‐June 2017) from the prospective, longitudinal, open‐label Amsterdam PrEP demonstration study, in which daily (dPrEP) and event‐driven PrEP (edPrEP) were offered to 374 HIV‐negative MSM and two transgender persons. Participants self‐selected the preferred PrEP‐regimen at baseline and could switch regimens at three‐monthly follow‐up visits. We measured motives for choosing PrEP‐regimen at baseline and for switching and stopping PrEP at follow‐up visits. Open‐ and closed‐end items were combined and qualitatively analysed. Results: Choices of PrEP‐regimens were determined by personal and contextual factors, involving the perceived self‐efficacy concerning adherence, the risk‐context, and the anticipated impact of PrEP on physical and sexual wellbeing. dPrEP was preferred because of the anticipated better adherence and the fear of side‐effects relating to edPrEP re‐initiations. Moreover, dPrEP was perceived to be more effective than edPrEP. Motives to choose edPrEP were the expected physical burden of dPrEP, anticipated side‐effects of dPrEP, and fear to forget daily doses. Regarding the risk‐context: dPrEP was preferred for unplanned and/or frequent sex, while edPrEP was chosen when risk was predictable and/or less frequent. While some chose for dPrEP to gain more sexual freedom, others chose for edPrEP to minimize sexual risk episodes. Changes in the above factors, such as changing risk patterns, changing relationships or changing physical conditions, resulted in switching regimens. Choices to stop PrEP were related to lower sexual risk, adherence issues and side‐effects. Conclusions: The great diversity of motives illustrates the importance of offering a choice of PrEP‐regimens. In counselling of MSM starting PrEP, choices for PrEP‐regimens may be addressed as a continuum of flexible and changeable options over time. This may help individuals choose the PrEP‐regimen that best fits their current sexual context, priorities and personal capabilities and therefore will be more easily adhered to.